Informal caregivers in Italy: the ‘phantom zone’ of welfare - Cioffi, Andrea; Cecannecchia, Camilla; Baldari, Benedetta; Karaboue, Michele Ahmed Antonio (Acta Biomedica Atenei Parmensis, 2023)
Medical progress and the consequent gradual ageing of the population increase the number of people in Europe who require continuous care, as they suffer from chronic diseases or senility. This demand is disproportionate if compared to the economic resources of health systems and is, therefore, heavily supported by the activity of the so-called "informal caregivers". With our article we propose to depict the current scenario in Italy, dwelling on the safeguards, to date, aimed at informal caregivers, which are insufficient to correct the criticalities associated with the burdensome assistance provided by such figures. Such critical issues result in a real risk for the health of informal caregivers and their loved ones and require urgent action by the health system. If it is true that health welfare is not able to protect the increasing number of people who are not self-sufficient, it is necessary to invest at least on specific measures to preserve the health and skills of those who are at the forefront of this hidden welfare. (www.actabiomedica.it)